Research of prospects for using zeolites in the food industry - Притульська, Наталія Володимирівна; Бондаренко, Євгенія Віталіївна (Eastern-European Journal of Enterprise Technologies, 2015)
The world experience of using zeolites in the food production was investigated. It was found that zeolites are used in the food industry to decolorize various mineral and vegetable oils and animal fats; purify water, alcoholic and soft drinks, juices, tea, vinegar, beer, wine from proteins, pesticide residues, heavy metals, toxic elements, toxins, mycotoxins, radionuclides and other xenobiotics; prevent caking of shredded cheese, flavor additives and flour. To reveal the possibility of using zeolites in developing detoxifying food products, their ability to remove xenobiotics from the human body was investigated. Given that almost all zeolites are used in medicine as highly effective sorbents, as evidenced by the positive results of their use in the treatment of poisoning, intoxication, gastrointestinal disorders, allergic reactions, etc., they can be used as raw materials in developing detoxifying food products for people who are faced with food, environmental or occupational poisoning in hazardous working conditions. The ability of zeolites to suppress pathogenic microflora of food systems and exhibit antimicrobial properties was examined, a positive experience of their use in agriculture as a fungicide and preservative for storing corn, root crops, sunflower seeds was revealed, which gives the basis for research towards finding methods to extend the shelf life of food products.